L2 Gain or L2 Pain? A Comparative Case Study of the Target Language Development among the Erasmus+ Mobility Students and At-Home Students - Ożańska-Ponikwia, Katarzyna; Carlet, Angélica; Pujol Valls, Maria (Theory and Practice of Second Language Acquisition, 2019)
The Erasmus+ exchange programme has become very popular, with the numbers of student sojourners growing each year. However, it was observed that not all students benefit equally from the study abroad (SA) experience (cf. Kinginger, 2008, 2009; Marijuan & Sanz, 2018; Mitchell, Tracy-Ventura & McManus, 2017; Regan, Howard & Lemée, 2009). Consequently, the main aim of the present study was to have a closer look at various factors that might contribute to the development of the target language among two small groups of students that self-selected themselves to do their language teaching practicum abroad, as a part of the Erasmus+ mobility program (n=6), or to do it at the local schools in the country of their residence (n=5). Both groups were examined prior their departure and after their arrival with a battery of tests that included: Oxford Placement test, Self-reported proficiency questionnaire, Oral proficiency test based on Cambridge Advanced exam, Language Engagement Questionnaire, Multicultural Personality Questionnaire(MPQ), Big Five Personality Questionnaire and Trait Emotional Intelligence Questionnaire (TEIQue). Our findings demonstrated that the majority of the Erasmus+ mobility program students examined in this study showed some greater linguistic progress when it comes to grammar and speaking in comparison to the home stay students. However, there were two cases that failed to progress after the stay abroad experience. Further analyses and interviews showed that some other factors like attitudes, language engagement and satisfaction from the Erasmus experience might in fact influence and shape target language development while abroad. At the same time, it could be speculated that in the case of researched informants their progress in grammar and speaking could be assigned mostly to the amount and quality of the language input outside of the classroom setting.